Aberrant Phase Transitions: Side Effects and Novel Therapeutic Strategies in Human Disease - Verdile, Veronica; De Paola, Elisa; Paronetto, Maria Paola (Frontiers in Genetics, 2019)
Phase separation is a physiological process occurring spontaneously when single-phase molecular complexes separate in two phases, a concentrated phase and a more diluted one. Eukaryotic cells employ phase transition strategies to promote the formation of intracellular territories not-delimited by membranes with increased local RNA concentration, such as nucleolus, paraspeclkes, P granules, Cajal bodies, P-bodies and stress granules. These organelles contain both proteins and coding and non-coding RNAs and play important roles in different steps of the regulation of gene expression and in cellular signaling. Recently, it has been shown that most human RNA-binding proteins (RBPs) contain at least one low-complexity domain, called prion-like domain (PrLD), because proteins harboring them display aggregation properties like prion proteins. PrLDs support RBP function and contribute to liquid-liquid phase transitions that drive ribonucleoprotein granule assembly, but also render RBPs prone to misfolding by promoting the formation of pathological aggregates that lead to toxicity in specific cell types. Protein-protein and protein-RNA interactions within the separated-phase can enhance the transition of RBPs into solid aberrant aggregates, thus causing diseases. In this review, we highlight the role of phase transition in human disease such as Amyotrophic Lateral Sclerosis (ALS), Frontotemporal Dementia (FTD) and in cancer. Moreover, we discuss novel therapeutic strategies focused to control phase transitions by preventing the conversion into aberrant aggregates. In this regard, the stimulation of chaperone machinery to disassemble membrane-less organelles, the induction of pathways that could inhibit aberrant phase separation and the development of Antisense Oligonucleotides (ASOs) to knockdown RNAs could be evaluated as novel therapeutic strategies for the treatment of those human diseases characterized by aberrant phase transition aggregates.